Ireland’s Fiscal Spending Multipliers - Ivory, Kate; Casey, Eddie; Conroy, Niall (The Economic and Social Review, 2020)
This paper estimates government spending multipliers for Ireland. We add to the existing literature on Ireland-specific fiscal spending multipliers in two key ways. First, we focus on measures of economic activity that remove distortions caused by foreign-owned multinational enterprises, thus allowing us to derive truer estimates of the impact on the domestic economy of changes in fiscal policy. Second, we employ a number of statistical approaches in order to sense-check the multiplier estimates we derive, including standard SVAR approaches, an expectations-augmented VAR (EVAR) approach, and estimates based on a large-scale structural model. Our results show that government investment can have positive and significant initial impacts on Irish output, though these effects tend to disappear and/or become statistically insignificant over the longer term. Other forms of fiscal spending do not have a statistically significant effect.